Teams that work : the seven drivers of team effectiveness - Tannenbaum, Scott I.; Salas, Eduardo (Ascent Audio, 2023)
Why do some teams thrive, while others struggle? In the modern workplace, employees collaborate. Managers are expected to be effective team leaders and employees are expected to be valued teammates. But many teams struggle. Being part of a struggling team can be unpleasant, but it can also hurt your career and waste company resources. In Teams That Work, Scott Tannenbaum and Eduardo Salas present the seven drivers of team effectiveness and the clearest recommendations on what really makes teams great. Applying the lessons they've learned from working with high-stakes, high-risk team situations to any kind of organization, they will dispel some of the most enduring myths (e.g., can you be both a star and a great team player?), feature the most useful psychological research, and share real-world illustrations of effective teams in action. Listeners will find actionable, evidence-based tips for being an effective team leader, a great team member, a supportive senior leader, or an impactful consultant.